A review of crop water productivity in the Mediterranean basin under a changing climate: Wheat and barley as test cases. (17th April 2022) - UnNisa, Zaib; Govind, Ajit; Marchetti, Marco; Lasserre, Bruno
Abstract: The ever‐increasing water demands in the agricultural sector of the Mediterranean basin region (MBR) under climate change warrants that crop water productivity (WP) is a pertinent topic for discussion. Considering this need, this study aims to synthesize the body of knowledge on WP focusing on the MBR. The study is based on two test cases: (1) wheat, because it is a basic staple food in high dietary demand in the region and (2) barley, because it is a climate‐resilient alternative that is extensively cultivated in severe water‐ and salinity‐stress conditions. These staple crops are strategically important for regional food security in the MBR, which covers southern Europe, North Africa and western Asia. The study tries to investigate the plausible reasons for yield and WP gaps in the region. Our meta‐analysis revealed that wheat and barley are very different in their spatial distributions, productions and stress resiliencies in the MBR. Under the large gamut of biophysical and socio‐economic constraints that affect crop production, it is observed that the northern and southern parts of the MBR have large capacity differences (institutional, infrastructural and technical) in cereal production. It is noted that the role of soil‐water management in improving WP is vital and plays a critical role in closing yield gaps across the MBR. Moreover, the scaling of stress‐tolerant varieties along with a package of agronomic practices can enhance WP, and thereby we can make the region adaptive to climate change, especially in terms of water stress. The literature revealed that the MBR, especially the southern parts encompassing North Africa and western Asia, critically lacks comprehensive experimental/observational evidence on the dynamics of field water balance. This knowledge is key to enhancing WP assessments using modelling approaches. The paper concludes that the MBR does have water‐saving potential; it simply needs planned adaptation measures to enhance WP at the local and regional scales with effective benchmark studies in future. Résumé: Les demandes en eau toujours croissantes dans le secteur agricole de la Région du Bassin Méditerranéen (RBM) sous l'effet du changement climatique constatent que la productivité de l'eau agricole (PE) est un sujet de discussion pertinent. Compte tenu de ce besoin, cette étude vise à synthétiser l'ensemble des connaissances sur la PE en se concentrant sur la RBM. L'étude se base sur deux cas d'essai: (1) le blé, car il s'agit d'un aliment de base à forte demande alimentaire dans la région et (2) l'orge, car il s'agit d'une alternative résiliente au climat qui est largement cultivée dans des conditions sévères de stress hydrique et salin. Ces cultures de base sont stratégiquement importantes pour la sécurité alimentaire régionale de la RMB, qui couvre la région du sud de l'Europe, de l'Afrique du Nord et de l'Asie occidentale. L'étude tente d'étudier les raisons plausibles des écarts dans le rendement et la productivité de l'eau dans la région. Notre méta‐analyse a révélé que le blé et l'orge sont très différents dans leurs distributions spatiales, leurs productions et leurs résiliences au stress dans la RBM. Dans le cadre de la large gamme de contraintes biophysiques et socioéconomiques qui affectent la production agricole, on observe qu'il existe de grandes différences de capacité (institutionnelle, infrastructurelle et technique) dans la production céréalière dans les parties nord et sud de la RBM. Il est à noter que le rôle de la gestion sol‐eau dans l'amélioration de la PE est vital et joue un rôle essentiel dans la réduction des écarts de rendement à travers la RBM. De plus, la mise à l'échelle de variétés tolérantes au stress ainsi qu'un ensemble de pratiques agronomiques peuvent améliorer la PE, nous pouvons ainsi rendre la région adaptative au changement climatique, en particulier en termes de stress hydrique. La littérature a révélé que la RBM, en particulier les parties méridionales englobant l'Afrique du Nord et l'Asie occidentale, manque sérieusement des preuves expérimentales/d'observation complètes sur la dynamique de l'équilibre hydrique sur le terrain. Cette connaissance est la clé pour améliorer les évaluations de la PE à l'aide d'approches de modélisation. Le document conclut que la RBM a un potentiel d'économie d'eau; il faut simplement prendre des mesures d'adaptation planifiées pour améliorer la PE aux échelles locales et régionales avec des études de référence efficaces à l'avenir.